2021
DOI: 10.3390/nano11092285
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Nanowires on Laser-Patterned PEN as Promising Biomaterials

Abstract: As inflammation frequently occurs after the implantation of a medical device, biocompatible, antibacterial materials must be used. Polymer–metal nanocomposites are promising materials. Here we prepared enhanced polyethylene naphthalate (PEN) using surface modification techniques and investigated its suitability for biomedical applications. The PEN was modified by a KrF laser forming periodic ripple patterns with specific surface characteristics. Next, Au/Ag nanowires were deposited onto the patterned PEN using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…It is obvious from Figure 1 that the pristine PEN showed a flat surface with a surface roughness of 4.27 nm. After laser modification, the polymer surface was transformed into coherent ripple structures (LIPSS) with pronounced surface roughness [ 22 , 24 , 39 ]. This dramatic change was related to the LIPSS formation; a complex process based on the redistribution of matter due to refraction and interference of incident radiation at the interface with different refractive indexes [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious from Figure 1 that the pristine PEN showed a flat surface with a surface roughness of 4.27 nm. After laser modification, the polymer surface was transformed into coherent ripple structures (LIPSS) with pronounced surface roughness [ 22 , 24 , 39 ]. This dramatic change was related to the LIPSS formation; a complex process based on the redistribution of matter due to refraction and interference of incident radiation at the interface with different refractive indexes [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deposition of Cu nanowires (CuNWs) on the rippled PEN was realized by vacuum evaporation under specific conditions according to our previous study [ 24 ]. However, the copper deposition in this work was accomplished only from one side of the ripple structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al further demonstrated that imidazole-capped chitosan–gold nanocomposites did not display hemolytic activity and significant toxicity towards L929 cell line [ 238 ]. Pryjmaková et al modified the surface of polyethylene naphthalate (PEN) by a 248 nm KrF excimer laser and subsequently, Ag and Au nanowires were incorporated onto the modified PEN surface by vacuum evaporation [ 239 ]. The resulted nanocomposites displayed antibacterial effects against Gram-negative bacteria ( E. coli ) and Gram-positive bacteria ( S. epidermidis ) via a 24-hr incubation drop plate test and were suggested as a non-toxic material by a WST-1 cytotoxicity test.…”
Section: Nanocomposite/nanohybrid Antibacterial Materialsmentioning
confidence: 99%
“…In contrast, intrinsically bacterial-repellent surfaces can be achieved through modified surface topographies [22,[26][27][28][29], where laser-fabricated surface structures in the microand sub-micrometer range demonstrated both, increased and reduced bacterial retention [30][31][32][33][34][35][36][37]. It was suggested that the specific shape of the bacteria plays a decisive role for their adhesion as well as the depth-to-period aspect ratio of laser-generated microstructures.…”
Section: Introductionmentioning
confidence: 99%